Sex, Love, and Migration Postsocialism, Modernity, and Intimacy from Istanbul to the Arctic - Bloch, Alexia (Cornell University Press, 2017)
A common image of migration in the early twenty-first century features young women from poor countries who are drawn into low paid, and often intimate, labor in wealthy countries. While aligning with scholarship critical of such inequalities, From Istanbul with Love traces how new mobilities are fundamentally reshaping emotional worlds and social ties between women and men, women and work, women and their households of origin, and women and children in the region. Based on ethnographic fieldwork spanning over a decade carried out primarily in Istanbul, but also in Russia and southern Moldova, Alexia Bloch moves between the lives of post-Soviet migrant women employed in three distinct spheres-sex work, the garment trade, and domestic work-to consider how they negotiate emotion, intimate relationships, and unpredictable state power shaping their labor and their relationships.